2016
DOI: 10.1590/1678-775720150451
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro evaluation of CAD/CAM vs conventional provisional crowns

Abstract: Objective This study compared the marginal gap, internal fit, fracture strength, and mode of fracture of CAD/CAM provisional crowns with that of direct provisional crowns.Material and Methods An upper right first premolar phantom tooth was prepared for full ceramic crown following tooth preparation guidelines. The materials tested were: VITA CAD-Temp®, Polyetheretherketone “PEEK”, Telio CAD-Temp, and Protemp™4 (control group). The crowns were divided into four groups (n=10), Group1: VITA CAD-Temp®, Group 2: PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
122
2
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(149 citation statements)
references
References 21 publications
15
122
2
10
Order By: Relevance
“…In this study, absolute marginal discrepancy was utilized to assess the adaptation of interim crowns and found a similar result, namely that manually fabricated interim crowns (group BAC) had significantly higher marginal discrepancy than CAD/CAM PMMA resin interim crowns (group CAM). Abdullah et al evaluated the marginal gap and internal fit of CAD/CAM interim crowns and direct interim crowns made of bis‐acryl composite resin material by using the silicone replica technique. They reported that CAD/CAM interim crowns demonstrated superior marginal and internal fit than manually fabricated interim crowns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, absolute marginal discrepancy was utilized to assess the adaptation of interim crowns and found a similar result, namely that manually fabricated interim crowns (group BAC) had significantly higher marginal discrepancy than CAD/CAM PMMA resin interim crowns (group CAM). Abdullah et al evaluated the marginal gap and internal fit of CAD/CAM interim crowns and direct interim crowns made of bis‐acryl composite resin material by using the silicone replica technique. They reported that CAD/CAM interim crowns demonstrated superior marginal and internal fit than manually fabricated interim crowns.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 3DP as an additive manufacturing method is believed to be more efficient in utilizing the material than the subtractive milling method . Recently, several studies suggest that CAD/CAM interim crowns have better marginal integrity than conventional manually fabricated interim crowns . However, there are limited data on the comparison between 3DP interim crowns and other manufacturing methods.…”
mentioning
confidence: 99%
“…From the perspective of the development of computer‐aided technologies, numerous computer‐aided tools become commercially available. Researches have shown CAD/CAM are outperformed conventional design approaches [1,33]. However, these software tools are application‐oriented while most of them are based on the theories in multiple disciplines.…”
Section: Evolution Of Manufacturing Technologies and Computer Aided Tmentioning
confidence: 99%
“…If this is not achieved, gingival inflammation can occur . Precise adaptation of the margins and contact points are as important as adequate preparation of the teeth …”
Section: Introductionmentioning
confidence: 99%
“…11,13 Precise adaptation of the margins and contact points are as important as adequate preparation of the teeth. [14][15][16][17][18] Functions of provisional restorations include:…”
Section: Introductionmentioning
confidence: 99%